Exploring the VAW method of writing among ESL Primary Pupils: conceptual paper - Dg Nursazwani Daud; Wardatul Akmam Din; Asmaa Abdul Hameed Alsaqqaf (2018)
The lack of writing skills among rural ESL primary school pupils in Malaysia has been identi?ed based on the school level assessments. Based on the teachers as the researchers’ perspectives, the problem of writing among these rural young learners is cause by the lack of vocabulary acquisition where they don’t have choices of words in expressing their ideas in writing. Therefore, the researchers propose method with a writing module focusing on vocabulary enhancement in improving the writing skills among these learners. This module i.e. the VAW Module uses the VAW Method that comprises of vocabulary enhancement (V), application and practice (A) and Writing (W) is anticipated to help the pupils to power up their writing before they undergo the Primary School Achievement Test (UPSR) in Year 6 i.e. the national examination taken by all students in Malaysia at the end of their sixth year in primary school before they leave for secondary school